2021
DOI: 10.1016/j.intimp.2021.107636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with mild COVID-19 following treatment with hydroxychloroquine in an outpatient setting

Abstract: The role of hydroxychloroquine (HCQ) in early outpatient management of mild coronavirus disease 2019 (COVID-19) needs further investigation. This study was a multicenter, population-based national retrospective-cohort investigation of 28,759 adults with mild COVID-19 seen at the network of Comprehensive Healthcare Centers (CHC) between March and September 2020 throughout Iran. The baseline characteristics and outcome variables were extracted from the national integrated health system database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Due to lack of sufficient evidence on an effective treatment for mild COVID-19 [27,28], most previous trials in outpatient settings have been focused on clinical characteristics and epidemiologic factors rather than therapeutic regimens [14,15,[19][20][21]. However, the results of a large national cohort study of 7,295 patients with mild COVID-19 showed that the early administration of HCQ is associated with a lower rate of hospitalization and mortality as well as the absence of serious complications [29]. Similarly, HCQ was administered for almost all patients in the study according to the national guideline.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lack of sufficient evidence on an effective treatment for mild COVID-19 [27,28], most previous trials in outpatient settings have been focused on clinical characteristics and epidemiologic factors rather than therapeutic regimens [14,15,[19][20][21]. However, the results of a large national cohort study of 7,295 patients with mild COVID-19 showed that the early administration of HCQ is associated with a lower rate of hospitalization and mortality as well as the absence of serious complications [29]. Similarly, HCQ was administered for almost all patients in the study according to the national guideline.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of HCQ on the outcome measures was maintained after adjusting for confounding factors and comorbidities. This effect remained significant whether patients were diagnosed based on positive RT-PCR or otherwise [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health agencies in Western countries have focused on contagion control measures (lockdown), late-stage hospitalized patients, intensive care units, and vaccination, but for reasons that are yet to be clarified, early treatment has not been emphasized [2][3][4]. In eastern countries such as China, India, Iran, and Saudi Arabia, where early treatment and prevention with repurposed antivirals, particularly hydroxychloroquine (HCQ), has been widely implemented [5][6][7][8], lower IFRs than Western countries, where early treatment with orally available molecules has been overlooked or even discouraged, have been reported [1]. In addition, countries using chloroquine or HCQ as a treatment from the start of the epidemic had a much slower dynamic in daily deaths [9].…”
Section: Introductionmentioning
confidence: 99%